Quantum API Gateways: Exploring the Future of Secure and Scalable Communication in Quantum Computing Environments - Anusha Kondam (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
As quantum computing advances, the need for secure and scalable communication in quantum environments becomes increasingly important. Quantum API Gateways have emerged as a promising solution to address this challenge. These gateways bridge classical and quantum communication, enabling the secure transfer of information between classical and quantum systems. Through advanced cryptographic techniques and quantum key distribution protocols, Quantum API Gateways provide high security for data transmission in quantum computing environments. They also offer a scalable approach, allowing for the seamless integration of quantum applications with existing classical systems. It enables the development of hybrid quantum-classical systems, which are crucial for harnessing the full potential of quantum computing. Quantum API Gateways allow for the efficient and reliable management of quantum resources, such as quantum processors and channels, by providing a standardized interface for developers to access this resource.